El agua es un bien común - Petrella, Riccardo (Revista Española de Desarrollo y Cooperación, 2023)
In this article, the author reflects on the great questions regarding the access and use of water: ¿is the access to water a right or a necessity?, ¿is it a global public good or a private good? ¿how should it be managed?. While reflecting on the unsustainable uses of this scarce good, Petrella also presents the answers that are being implemented to control and manage the water including those leading to privatization. Finally, it also presents the three possible scenarios that may occur in the near future according to the level of commitment and the measures adopted around this issue.